Design and fabrication of mini cooling fridge using peltier / Muhammad Adam Abdullah - Abdullah, Muhammad Adam (2023)
This project aims to improve energy efficiency by using a Peltier instead of a compressor. The utilization of compressors contributes to higher power consumption thus increasing the electric cost. The cost of the compressor itself is relatively higher compared to a Peltier. For example, the usage of a compressor in the fridge. This study aims to tackle the above problems by introducing the utilization of Peltier as the cooling agent in the Fridge. The cold side of the Peltier will be attached to the inner aluminum plate inside the fridge and the hot part will be attached to an aluminum plate, heat sink and fans performed as the radiator. The power will be supplied by a 12V AC adapter and extruded polystyrene will act as thermal insulator. By applying the above method, the electricity bills and production cost of a fridge will be reduced